Kontra kurakot [videorecording] graftbusters - Monson, Winnie (Philippine Center for Investigative Journalism and GMA News and Public Affairs, 2000)
A topic considered difficult to film, Corruption has rarely been tackled in documentaries in the Philippines. Graftbusters dispels that the notion and investigates what people are doing to fight graft and corruption - from citizens of Abra watching over public funds meants for roads and bridges, Makati businessmen fighting extortion by corrupt tax agents to born-again Christian government employees who have taken up the cause of cleansing the corrupt Philippines bureaucracy.